Opinions and clinical practice of functional movement disorders: a nationwide survey of clinicians in China - Xin-Yi Xie (BMC, 2021)
Abstract Background There is rare reports about opinions and clinical practice of functional movement disorders (FMD) in China. The present survey aimed to investigate the views of FMD in Chinese clinicians. Methods The Chinese version survey of FMD were conducted in nationwide practitioners by means of an online questionnaire. Results Four hundred and thirty-four Chinese clinicians completed a 21-item questionnaire probing diagnostic and management issues in FMD. More than 80% of respondents considered that atypical movement disorder, multiple somatizations, and emotional disturbance were essential or absolutely necessary for clinically definite diagnosis of FMD. About three quarters of respondents requested standard neurological investigations to rule out organic causes. Over half believed that prior diagnosis of an organic disorder (59.9%), lack of associated non-physiologic deficits (51.8%), and evidence of physical injury (50.0%) were ‘very influential’ or ‘extremely influential’ for a non-FMD diagnosis. The majority (77.4%) of the respondents may refer patients to a neuropsychiatrist or psychiatrist experienced in FMD, followed by psychologist or psychotherapist experienced in FMD (53.2%). However, lack of guidelines, physician knowledge, and training often limited clinicians’ ability in managing patients with FMD. Early diagnosis of FMD, identification and management of concurrent psychiatric disorder, and acceptance of the diagnosis by the patient were considered most important for predicting a favorable prognosis. Conclusions Opinions and clinical practice of Chinese practitioners not only varied among Chinese neurologists, but also differed from international peers. Combined efforts are needed to promote related research and establish practice guidelines in China in the future.